ROLE OF BMI1 IN PROMOTING BREAST CANCER TUMORIGENESIS THROUGH ATTENUATING THE DNA DAMAGE RESPONSE PATHWAY - MacKenzie, Colleen (My University, 2018)
Breast cancer (BC) is a complex disease with over 25,000 new diagnoses made in Canadian women every year. The disease can be caused by inactivation of the ataxia telangiectasia mutated (ATM) pathway, a major anti-tumor mechanism that protects against the abnormal cell division and growth that occurs in breast cancer, but how the pathway is inactivated has yet to be completely elucidated. BMI1 is an established oncogene that is overexpressed in BC and is associated with poor disease prognosis. BMI1 is a component of the polycomb repressive complex 1 (PRC1) that acts to repress transcription of the ARF/INK4A locus encoding two important tumor suppressor genes. We have recently shown a novel property of BMI1 in attenuation of ATM function independent of this locus. We thus hypothesize a role of BMI1 in promoting BC formation through inhibiting oncogene-induced ATM activation, allowing cancer-promoting genes to induce abnormal cellular growth. To examine this hypothesis, we transiently expressed oncogene c-Myc with or without BMI1 co-expression. As expected, ectopic c-Myc expression upregulated γH2AX, a demonstrated target of ATM; concurrent BMI1 expression reduced the γH2AX levels. Similar observations were also obtained using a BMI1 mutant deficient in promoting PRC1-mediated repression of the ARF/INK4A locus. These observations support the concept that BMI1 contributes to ATM inactivation during BC tumorigenesis through mechanisms independent of PRC1. To further examine this concept, we investigated the association of γH2AX and BMI1 in vivo. In MCF7 cell-produced xenograft tumors, the presence of γH2AX nuclear foci was clearly observed, indicative of ATM activation during BC tumorigenesis. In xenografts generated by MCF7 cells stably expressing BMI1, a trend of reduction in γH2AX nuclear foci was observed. To further model BMI1’s pathological relevance in c-Myc induced BC under a more physiological setting, we are developing transgenic mouse models (GEM) with breast-specific c-Myc expression with or without a breast-specific BMI1 knockout. The goal of these experiments is to recapitulate the above in vitro and in vivo observations. The expectation, should it be achieved, will significantly strengthen the connection between BMI1 and ATM during breast cancer tumorigenesis.
Keywords: Breast Cancer; BMI1; ATM; c-Myc